2010
DOI: 10.1038/mp.2010.96
|View full text |Cite
|
Sign up to set email alerts
|

GWA study data mining and independent replication identify cardiomyopathy-associated 5 (CMYA5) as a risk gene for schizophrenia

Abstract: We conducted data-mining analyses using the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) and molecular genetics of schizophrenia genome-wide association study supported by the genetic association information network (MGS-GAIN) schizophrenia data sets and performed bioinformatic prioritization for all the markers with P-values ≤0.05 in both data sets. In this process, we found that in the CMYA5 gene, there were two non-synonymous markers, rs3828611 and rs10043986, showing nominal signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 53 publications
3
54
0
4
Order By: Relevance
“…These two SNPs showed nominally significant associations among the replication samples (rs2709370 Supplementary Table S5. The odds ratios in the cumulative analysis are comparable with other genes reported as significantly associated with psychiatric disorders in larger meta-analyses 59,60 and exceed the Venice interim criteria for 'small summary' findings. 61 Taken collectively, the association analysis suggests that SNPs in CREB1 may confer risk of BD among Europeans.…”
Section: Creb1 Variants Confer Risk Of Bdsupporting
confidence: 65%
See 1 more Smart Citation
“…These two SNPs showed nominally significant associations among the replication samples (rs2709370 Supplementary Table S5. The odds ratios in the cumulative analysis are comparable with other genes reported as significantly associated with psychiatric disorders in larger meta-analyses 59,60 and exceed the Venice interim criteria for 'small summary' findings. 61 Taken collectively, the association analysis suggests that SNPs in CREB1 may confer risk of BD among Europeans.…”
Section: Creb1 Variants Confer Risk Of Bdsupporting
confidence: 65%
“…65 Many studies reported psychosis risk genes, although they did not reach genome-wide significance in the initial GWAS samples, they later showed consistent replications in multiple independent samples, such as CMYA5, VRK2 and FGFR2. 59,60,[66][67][68] In small sample sets (<300 cases), association of CREB1 with BD has previously been reported, [69][70][71] with one study finding nominal significant association for the CREB1 variant. However, due to the small sample size and lack of replications, the possibility of falsepositive results in their study could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, even these risk genes can only explain a small portion of the genetic liability, and the missing heritability is still unclear. A recent aggregated analyses [13] indicated that SCZ and BPD are polygenic disorders involving multiple susceptibility variants, with each of them having a tiny effect on the risk, and there may be true findings among those markers passing only nominal significance in the initial GWAS of psychiatric disorders, but later were consistently replicated in independent samples, such as CMYA5 [55], FGFR2 [56], CAMKK2 [57], and CREB1 [30]. Hence, dissection of the GWAS datasets is still valuable for further identification of the risk genes, and we believe this is also one of the most important contributions of GWAS.…”
Section: A Non-synonymous Snp Rs5174 In Lrp8 Is Associated With Schizmentioning
confidence: 99%
“…With a two-stage design, by integrating data-mining and functional analyses of a selected number of candidates from GWAS datasets, we found that two markers in the CMYA5 gene are associated with SCZ [31] ; one of the markers (rs10043986) changes a proline to leucine in the protein sequence. Using a convergent functional genomics approach, which utilizes poly-evidence scoring and pathway analyses, Ayalew et al identified several genes involved in SCZ, including DISC1 and TCF4 [32] .…”
Section: Common Variants Contributing To Sczmentioning
confidence: 99%